Modal sosial paguyuban dalam pengembangan fasilitas pendidikan di sekolah dasar - Yolanda Stepy; Firman Firman (Indonesian Institute for Counseling, Education and Therapy (IICET), 2020)
This study aimed to describe the social capital of the community in developing educational facilities in SD Negeri 005 State Petapahan Jaya, Kampar District. With the reality of a heterogeneous population inhabited by self-employed trans-migrants consisting of Sundanese, Batak, Minang, Malay, and Javanese. Economically the village had developed significantly, especially since the opening of the Palm Oil plantation. This research used a qualitative approach. Data collection was done through observation, interviews and document use. Data analysis techniques used in this study are data reduction, data presentation and conclusion drawing. The results of this study indicate that there were three elements of community social capital in developing educational facilities in SD Negeri 005 Petapahan Jaya, Kampar Regency: (1) Social Networking, in the form of community participation and solidarity (2) Trust in the form of honesty and cooperation (3) The existence of norms that jointly owned.